Guinness world records 2015 : inside, all new augmented reality! - Glenday, Craig ([Place of publication not identified] : Guinness World Records Limited, 2014)
The world's best-selling annual is back with thousands of exciting new records. Plus, enjoy special features on records through the decades to help us celebrate our 60th anniversary, and have a play with this year's jaw-dropping augmented-reality app with interactive animations and games that bring the book to life!
Includes index.
Keywords: WORLD RECORDS; CURIOSITIES AND WONDERS